THE PROBLEM OF THE OPTIMAL VOLUME OF ENTERPRISE PRODUCTION IN THE LIGHT OF THE THEORY OF TRANSACTION COSTS AND THE PRACTICE OF OUTSOURCING - Sławomir Jarka (Acta Scientiarum Polonorum. Oeconomia, 2018)
The purpose of the article was to determine the importance of outsourcing and transaction costs accompanying it in the process of optimizing company structures. The practical reference of the adopted research objective was to indicate the optimal size of the enterprise. The aim is also to indicate, based on literature research, the impact of the transaction cost theory on the development of outsourcing. The findings of research show that the optimal size of the enterprise corresponds to the production volume at which the transaction function indicates the decreasing level of their marginal product, until the value reaches 0. With a high specificity of the company’s resources, which requires the use of specific technologies, there are transaction costs on this account that shape the price of the goods being the subject of the transaction. Thus, when further increasing the size of the production company, one should also take into account the added transaction costs, among others, control and monitoring of transactions. Modern enterprises focus their actions on key areas of activity. They give up production of what outsourcing providers can do more effectively, leaving what is specific for a given product, determining the company’s identity and the essence of production.